Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae) - Yang, Lian-Fang; Yuan, Hong-Yin; Morse, John C. (Zootaxa, 2017)
The Chinese species of the genera Lannapsyche and Marilia (Trichoptera, Odontoceridae) are reviewed, including 1 new species of Lannapsyche (Lannapsyche altilis sp. n.), 1 new Chinese record of Lannapsyche (Lannapsyche chantaramongkolae Malicky 1989, originally described from Thailand), and 3 new species of Marilia (Marilia discaulis, sp. n., Marilia megalopos, sp. n., and Marilia qinlingensis, sp. n.), bringing the Chinese fauna of Lannapsyche to 3 species and of Marilia to 6 species. Previously known species Lannapsyche setschuana Malicky 1995b and Marilia parallela Hwang 1957 are redescribed and reillustrated for both males and females. Updated information about the holotype specimen of Marilia simulans Forsslund 1935 is provided. Distinctive differences of the female genitalia are described, which may add important diagnostic characters for genus and species recognition.